2019
DOI: 10.2147/cmar.s194523
|View full text |Cite
|
Sign up to set email alerts
|

<p>Acute myeloid leukemia patient with <em>FLT3-ITD</em> and <em>NPM1</em> double mutation should undergo allogeneic hematopoietic stem cell transplantation in CR1 for better prognosis </p>

Abstract: Background: According to the recent National Comprehensive Cancer Network (NCCN) guidelines, the risk level in acute myeloid leukemia (AML) patients with FLT3-ITD and NPM1 double mutation (AML FLT3-ITD+/NPM1+) depends on the allelic ratio of FLT3-ITD. But despite a low or high allelic ratio of FLT3-ITD, AML FLT3-ITD+/NPM1+ patients belong to the favorable or intermediate risk, for whom allogeneic stem cell transplantation is not obligated. However, some latest studies pointing out that NPM1 and FLT3-ITD double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
(54 reference statements)
1
15
0
Order By: Relevance
“…Loghavi and colleagues reported that AML FLT3 -ITD +/NPM1+ patients with a DNMT3A mutation had shorter event-free survival compared to those in other mutation groups [ 61 ]. Similarly, recent studies have suggested that AML patients with concomitant DNMT3A R882+ /FLT3 -ITD +/NPM1+ mutations had a very poor prognosis, and allo-HSCT could moderately improve their survival [ 62 , 63 ]. Our study cohort included 21 AML FLT3 -ITD +/NPM1+ patients, 4 of whom had a DNMT3A R882 mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Loghavi and colleagues reported that AML FLT3 -ITD +/NPM1+ patients with a DNMT3A mutation had shorter event-free survival compared to those in other mutation groups [ 61 ]. Similarly, recent studies have suggested that AML patients with concomitant DNMT3A R882+ /FLT3 -ITD +/NPM1+ mutations had a very poor prognosis, and allo-HSCT could moderately improve their survival [ 62 , 63 ]. Our study cohort included 21 AML FLT3 -ITD +/NPM1+ patients, 4 of whom had a DNMT3A R882 mutation.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies indicated that allogeneic SCT improves the prognosis in NPM1mutated AML with FLT3/ITD low AR 24,25 . Recently, Huang et al 26 found that SCT have better survival in adult AML patients with both NPM1 and FLT3/ITD mutations comparing to chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…In CEBPA bi+ AML patients with sustained positive MRD after two consolidation cycles, the loss of negative MRD status at any time was the only independent risk factor for CIR, leukemia-free survival (LFS) and OS, while allo-HSCT achieved superior 3-year CIR (0% vs. 52.8%, p = 0.006) and LFS (88.9% vs. 47.2%, p = 0.027) rates compared to chemotherapy in MRD + patients in single center studies [ 20 , 21 ]. Among AML patients with nucleophosmin 1 (NPM1) mutation in single center study, those with MRD detected by both multiparameter flow cytometry (FCM) and real-time quantitative polymerase chain reaction (qRT-PCR) were classified as a subgroup with a high relapse risk (46–83%) following chemotherapy [ 22 ]; allo-HSCT reduced the CIR and improved DFS in NPM1 + AML in CR1 patients, especially those positive for FMS-like tyrosine kinase 3 internal tandem duplication (FLT3-ITD) [ 23 ]. Therefore, MRD-directed risk stratification and the identification of additional risk factors would help guide transplant decisions for patients with fav-AML in CR1 (Table 1 ).…”
Section: Indications and Timing Of Allo-hsctmentioning
confidence: 99%